VD_FINDINFO Jug / 2011 / 107 vom 14. Juni 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, MOTIF DE RÉVISION, RÉVISIONDÉCISION | 410 al. 1 let. b CPP (CH), 411 CPP (CH), 428 al. 3 CPP (CH)